Rancang Alat Rewinding Motor Listrik dengan Kendali PLC - Tri Isra Janwardi (LPPM Politeknik Jambi, 2019)
Electrical Motor is the familiar machines to operate all of the industrial system. The high frequency of using the electrical motor is made the motor work harder. The effect of that all is made the conductor is lose of insulator. The electrical motor that has not good winding is not good to use in industrial machine. The electrical motor that has fired winding is need to rewind. Rewinding machines nowaday is familiar using manual vehichles. That using human energy to operate the rewinding machines. That why need to design the automatically rewinding machines with PLC’s control and DC electrical motor as the crank. The result of this research is the winding of this rewinding machines is more prices than manual rewinding machines. The component that needed in this machines those are: PLC as the program controller of rewinding machines, NO pushbutton switch as input component, 24 VDC of DC electrical motor as crank of rewinding machines, alumunium metal and wood as winding spot. As the protection, using the 2A MCB with C-Class type for lighting and home electronics device. As the application, this machines can use to make 150 of winding at 17.5 minutes.